Diagnostic Value of Autoantibodies Against Citrullinated Peptide Antigens in Rheumatoid Arthritis: Comparison of Different Commercial Kits - Özlem ŞAHİN,; Ece KAPTANOĞLU,; Mustafa Zahir BAKICI,; Hafize SEZER,; Hasan ELDEN,; Sami HİZMETLİ, (Archives of Rheumatology, 2011)
Objectives: In this study we tested the diagnostic values of rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP) and two different commercial anti-mutated citrullinated vimentin (anti-MCV) kits in the differential diagnosis of rheumatoid arthritis (RA) considering that there might also be substantial differences between the performances of the commercial kits. Patients and methods: T hirty-four R A p atients, a dmitted t o our rheumatology outpatient clinics between October 2008 and February 2009, and 24 healthy controls were included in this study. Sera of RA patients and healthy controls were analyzed for RF, anti-CCP-2, anti-MCV-548 and anti-MCV-248 autoantibodies with two different commercial kits. Disease activity was determined by disease activity score 28 (DAS-28) in RA patients. Extra-articular involvement was evaluated in RA patients. Results: In the receiver operating characteristic (ROC) curve analysis perfomed to determine the diagnostic sensitivity, anti- CCP-2 had the highest value of area under ROC curve. Sensitivity and specificity was 88% and 90%, 84% and 100%, 80% and 90%, and 84% and 100% for RF, anti-CCP-2, anti-MCV-548, and anti-MCV-248 respectively. DAS-28 had a weak correlation with anti-CCP-2 (r=0.623), anti-MCV-548 (r=0.481), and Anti-MCV-248 (r=0.408). There was no statistically significant difference in RF, anti-CCP-2, anti-MCV-548, and anti-MCV-248 values between patients with or without extra-articular involvement or between patients with low or moderate disease activity according to DAS-28 score. Conclusion: A nti-CCP, R F a nd a nti-MCV a utoantibodies a re a ll useful in the differential diagnosis of RA. However, the anti-CCP antibody has a superior diagnostic value compared to the other autoantibodies. The anti-MCV antibodies detected by the anti- MCV-248 kit seem more reliable than the anti-MCV antibodies detected by the anti-MCV-548 kit in differential diagnosis of RA due to their high sensitivity and specificity. These findings suggest that different commercial kits may exhibit different performances. Nevertheless, our results need to be confirmed by future studies which should include more patients.